What makes a monster? : discovering the world's scariest creatures - Keating, Jess; DeGrand, David (New York : Alfred A. Knopf, 2017)
"An informative introduction to nature's scariest creatures, exploring why some animals are considered 'monsters.'"-- Provided by publisher.
School Library Journal, July 2017
Publisher's Weekly, July 2017
Bulletin (Center for Children's books), July 2017
Kirkus Review, May 2017
5.0
K-3
Keywords: Animals -- Miscellanea -- Juvenile literature; Dangerous animals -- Juvenile literature; Animals -- Miscellanea; Dangerous animals